Pathogenicity, sequence and phylogenetic analysis of Malaysian Chicken anaemia virus obtained after low and high passages in MSB-1 cells - Chowdhury, S.M.Z.H.; Omar, A.R.; Aini, I.; Hair-Bejo, M.; Jamaluddin, A.A.; Md-Zain, B.M.; Kono, Y. (Springer, 2003)
Specific-pathogen-free (SPF) chickens inoculated with low passage Chicken anaemia virus (CAV), SMSC-1 and 3-1 isolates produced lesions suggestive of CAV infection. Repeated passages of the isolates in cell culture until passage 60 (P60) and passage 123 produced viruses that showed a significantly reduced level of pathogenicity in SPF chickens compared to the low passage isolates. Sequence comparison indicated that nucleotide changes in only the coding region of the P60 passage isolates were thought to contribute to virus attenuation. Phylogenetic analysis indicated that SMSC-1 and 3-1 were highly divergent, but their P60 passage derivatives shared significant homology to a Japanese isolate A2.